Will college pay off? : a guide to the most important financial decision you'll ever make - Cappelli, Peter (PublicAffairs, 2015)
The decision of whether to go to college, or where, is hampered by poor information and inadequate understanding of the financial risk involved. Adding to the confusion, the same degree can cost dramatically different amounts for different people. A barrage of advertising offers new degrees designed to lead to specific jobs, but we see no information on whether graduates ever get those jobs. Mix in a frenzied applications process, and pressure from politicians for relevant" programs, and there is an urgent need to separate myth from reality.